Delta is a ventral to dorsal signal complementary to Serrate, another Notch ligand, in Drosophila wing formation. - Dan Doherty; Georg Feger; Susan Younger-Shepherd; Lily Yeh Jan; Yuh Nung Jan (1996)
Wing margin formation in Drosophila requires the Notch receptor and, in the dorsal compartment, one of its ligands, Serrate. We provide evidence that Delta, the other known ligand for Notch, is also essential for this process. Delta is required in ventral cells at the dorsal/ventral compartment boundary, where its expression is specifically elevated in second-instar wing discs during wing margin formation. Moreover, ectopic Delta expression induces wingless, vestigial, and cut and causes adult wing tissue outgrowth in the dorsal compartment. The effect is mediated by Notch, because loss of Notch activity suppresses Delta-induced ectopic wing outgrowth. Whereas ectopic expression of Notch or the truncated activated Notch induces cut in both dorsal and ventral compartments, ectopic Delta expression induces cut only in the dorsal compartment and ectopic Serrate induces cut only in the ventral compartment. These observations indicate that Notch-expressing cells in a given compartment have different responses to Delta and Serrate. We propose that Delta and Serrate function as compartment-specific signals in the wing disc, to activate Notch and induce downstream genes required for wing formation.